2022
DOI: 10.1177/21501319221138196
|View full text |Cite
|
Sign up to set email alerts
|

Real World Evidence and Clinical Utility of KidneyIntelX on Patients With Early-Stage Diabetic Kidney Disease: Interim Results on Decision Impact and Outcomes

Abstract: Introduction and Objective: The lack of precision to identify patients with early-stage diabetic kidney disease (DKD) at near-term risk for progressive decline in kidney function results in poor disease management often leading to kidney failure requiring unplanned dialysis. The KidneyIntelX is a multiplex, bioprognostic, immunoassay consisting of 3 plasma biomarkers and clinical variables that uses machine learning to generate a risk score for progressive decline in kidney function over 5-year in adults with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…6, 8 - 10 The reasons for this are multifactorial, but a lack of early and accurate risk stratification to identify those most at risk for DKD progression is a key problem. 8 , 11 Therapeutic inertia is common in kidney disease, due to inadequate ability to determine who will derive the most (absolute) benefit from new treatments for a silent condition that takes years to realize the gains of therapy on a patient-level basis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6, 8 - 10 The reasons for this are multifactorial, but a lack of early and accurate risk stratification to identify those most at risk for DKD progression is a key problem. 8 , 11 Therapeutic inertia is common in kidney disease, due to inadequate ability to determine who will derive the most (absolute) benefit from new treatments for a silent condition that takes years to realize the gains of therapy on a patient-level basis.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported on the 6-month interim results of a real-world evidence (RWE) study using the KidneyIntelX test, which demonstrated changes in clinical management of patients with T2D and early-stage (Grade (G)1-G3) DKD. 11 Here, we sought to ascertain the 1-year data from the RWE KidneyIntelX program at MSHS. Our focus was on sustainability of the KidneyIntelX testing platform as a program of personalized risk assessment with an emphasis on treatment with cardio-renal protective agents, utilization of consult services, advanced practice provider driven protocols post-testing, and impact on A1C, UACR, and the eGFR slope as drivers of patient-provider compliance and improved outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…All patients had T2D and established DKD at baseline, with an eGFR of 30 to 59 mL/min/1.73 m 2 or an eGFR ≥60 mL/min/1.73 m 2 with albuminuria (uACR ≥30 mg/g). 17,20,21 2.1 | Study populations…”
Section: Methodsmentioning
confidence: 99%
“…The laboratory assay of the kidneyintelX.dkd test quantitatively measures K2EDTA plasma TNFR1, TNFR2 and KIM‐1, and combines these measurements with clinical data to produce a level of risk (low, moderate or high) associated with PDKF for adult patients with T2D and CKD (ie, DKD). All patients had T2D and established DKD at baseline, with an eGFR of 30 to 59 mL/min/1.73 m 2 or an eGFR ≥60 mL/min/1.73 m 2 with albuminuria (uACR ≥30 mg/g) 17,20,21 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation